2019
DOI: 10.1371/journal.pone.0220016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic profile of admitted victims in a tertiary hospital after the 2015 earthquake in Nepal

Abstract: Background In 2015, an earthquake killing 9,000 and injuring 22,000 people hit Nepal. The Tribhuvan University Teaching Hospital (TUTH), a reference tertiary hospital, was operational immediately after the earthquake. We studied the profile of earthquake victims admitted in TUTH and assessed what factors could influence hospital length of stay. Methods An earthquake victim dataset was created based on patient records, with information on sex, age, date of admission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Victims of earthquake-related disasters may present with a wide spectrum of injuries and severities [22][23][24]. In the present study, traumatic injuries were predominant, followed by burns and inhalation injuries.…”
Section: Discussionmentioning
confidence: 61%
“…Victims of earthquake-related disasters may present with a wide spectrum of injuries and severities [22][23][24]. In the present study, traumatic injuries were predominant, followed by burns and inhalation injuries.…”
Section: Discussionmentioning
confidence: 61%
“…Shortly after, there is a need for hospital care for trauma-related complications, which could explain why admissions due to factors influencing health status and contact with health services are high in EQ1 and EQ2. A previous study identified this diagnostic category in some of the earthquake victims who were admitted in TUTH 15 . The high probability of admissions in this category in post-EQ may be due to an accumulation of interventions that re-started after weeks of being interrupted, such as the donation of organs and tissues by healthy donors.…”
Section: Discussionmentioning
confidence: 95%
“…The fact that injury admissions occurring in EQ1 were particularly long may relate to earthquake injury characteristics linked with severity and frequent complications 24 , or because many severe cases were probably referred to TUTH since it is a reference hospital, and it was functional after the earthquake 15 . In addition, external factors may have increased LOS: a disrupted transport network, or destroyed housing, may have delayed patient discharge until an improvement of the situation.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the previous studies on earthquake victims during earthquakes in Iran, China, Pakistan and Nepal whose findings suggest that the majority of survived victims sustained lower limb injuries. 14 , 15 , 16 , 17 , 18 We may presume that the reason for the increased frequency of lower limb injuries during earthquakes is that people during earthquakes rush panicky out of the houses and therefore suffer lower extremity injuries. However, this supposition requires further research to be fully understood.…”
Section: Discussionmentioning
confidence: 99%